Demand and Supply of Vegetables and Fruits During Pandemic Covid-19 at the Downtown of Jember Regency - Henik Prayuginingsih; Nurul Fathiyah Fauzi; Nur Muhammad Ferdiansyah; Faizha Dea Maulidiyah (Nusantara Science and Technology Proceedings, 2022)
People try to fulfill their need for food during the pandemic Covid-19, both in quantity and kind of food that have vitamins and minerals which are good for keeping dan increasing immunity, such as vegetables and fruits. This study aimed to identify if there was a difference in (1) the demand for vegetables and fruits, and (2) the supply of vegetables and fruits before during the pandemic Covid-19 at the downtown of Jember Regency. The method of study was descriptive-analytic with 100 samples, consisting of consumer and green groceries of vegetables and fruits. Data were analyzed by t-test paired samples. The result was: (1) demand for vegetables decreased during the pandemic Covid-19 as described below: (a)green vegetables at the traditional market were decreased21.25%, another vegetable decrease61.61% and they were significant at5% dan 10% test level, (c) green vegetables at modern market decreased 11.76% and another vegetable increased23.57 % but they were not significant (2) demand of fruits : (a) decreased 57.28% at a traditional market and significant at 5% level (b) increased 16.67 % at the modern market but not significant, (3) supply of vegetables when the study was done (January) decreased 28.88% and significant at 10% test level, meanwhile supply of fruits decreased 56.00% and significant at 1% test level.